2003
DOI: 10.1095/biolreprod.102.003699
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Sexual Immaturity in Male Mice and Bucks by Immunization Against N-Terminal Peptides of the Follicle-Stimulating Hormone Receptor1

Abstract: The follicle-stimulating hormone is one of the two pituitary hormones that control fertility in both sexes. In the male, receptors for FSH (FSHR) are only expressed on testicular Sertoli cells. FSH plays different roles during the male life; it functions as a growth factor during development and sustains spermatogenesis in adults. However, the exact role of this hormone as an initiator of male fertility is not fully understood and few data are available concerning its involvement during the peripubertal period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Comparable with previous studies, the onset of puberty in this study is characterized by high mean LH concentrations at about 12 -14 weeks of age that is suggested to induce testicular growth and spermatogenesis in pubescent goat kids. The relatively high concentrations of FSH are reported to enhance the production of steroid biosynthetic enzymes and increase the formation of LH receptors in the testis followed by increased production of testosterone (Foster 1994, Hall 1994, Ahmad et al 1996, Brooks et al 1996, Foster et al 2002, Abdennebi et al 2003. In conformity with the female kids in our parallel study (Lyche et al 2004a), the PCB153-exposed male kids showed a significant effect of treatment on the mean plasma LH concentration.…”
Section: Discussionsupporting
confidence: 69%
“…Comparable with previous studies, the onset of puberty in this study is characterized by high mean LH concentrations at about 12 -14 weeks of age that is suggested to induce testicular growth and spermatogenesis in pubescent goat kids. The relatively high concentrations of FSH are reported to enhance the production of steroid biosynthetic enzymes and increase the formation of LH receptors in the testis followed by increased production of testosterone (Foster 1994, Hall 1994, Ahmad et al 1996, Brooks et al 1996, Foster et al 2002, Abdennebi et al 2003. In conformity with the female kids in our parallel study (Lyche et al 2004a), the PCB153-exposed male kids showed a significant effect of treatment on the mean plasma LH concentration.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, there is an urgent need for a better contraceptive method that is acceptable, effec-tive, reversible and available both in the developed and in the developing nations. 8,9 With respect to gamete-associated components, research has focused on the relationship between sperm antigens and fertility in past decades. Mammalian reproduction begins with the production of male and female gametes followed by their unification within a fertilized egg.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The ECD of FSH receptor (FSHR) has also been considered a suitable target for a male vaccine, as it is expressed exclusively on testicular Sertoli cells. 8,9 With respect to gamete-associated components, research has focused on the relationship between sperm antigens and fertility in past decades. Among numerous molecular candidates related to sperm, epididymis protease inhibitor (Eppin) is a promising candidate.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution pattern of FSHR permits its use in tumor‐targeting therapy strategies . Additionally, the ECD of FSHR has been used as an immunogen to produce a contraceptive vaccine . However, the recognition and specific binding of FSH to its receptor have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%